Pengaruh Latihan Kecepatan Terhadap Keterampilan Dribbling Pada Pemain Sepak Bola Di Klub Lubuk Sahung Kebupaten Seluma - Fahriansyah Dito; Mariska Febrianti; Ajis Sumantri (UNIVED Press, Universitas Dehasen Bengkulu, 2026)
This study aims to determine the effect of speed training on the dribbling skills of soccer players from the Lubuk Sahung Club, Seluma Regency. This research is an experimental study. The sample size for this study was all 18 Lubuk Sahung Club soccer players. The results of the hypothesis testing for the entire group were obtained. The initial test, conducted on 18 soccer players from the Lubuk Sahung Club, Seluma Regency, yielded a highest score of 11.24, a lowest score of 17.81, with a mean of 14.26 and a standard deviation of 1.76. The final test yielded a highest score of 9.20 and a lowest score of 16.2. Data analysis yielded a mean of 12.27 with a standard deviation of 1.77. The instrument used in this study is soccer dribbling skills, based on the pre-test and post-test data of the dribbling skills of the Lubuk Sahung club's soccer game in Seluma district, the results of the normality test were obtained which were all normally distributed. Based on the initial test and final test measurements using the group t-test statistical approach, the overall training method t count = 8.29 and t table (α = 0.05) = 1.74, which means t count > t table.